TAKHRIJ AL-HADITH IN MU’JAM AL-KABIR: THE PROHIBITION OF OVEREATING IN ISLAM - Nasution, Alhafidh; Nurdiana, Evi; Rohmah, Qonitatu Zulfatu (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
This research is motivated by the fact that many Muslims are not aware of the urgency of studying the science of hadith and its implementation in life. Therefore, this study aims to examine a hadith related to the prohibition of excessive eating in the book Mu’jam al-Kabir by Imam at-Thabrani as one of the efforts in implementing the science of hadith. This study also aims to provide understanding to the Muslim community to avoid diseases that harm health due to overeating. The result of this research is that in the book Mu’jam al-Kabir, it is explained that the Prophet Muhammad likened people who overeat to unbelievers who are less grateful for the favor of Allah. On the contrary, it is said that a grateful believer will understand how to be right with Allah and not make material things the purpose of his life. Therefore, it can be seen the difference in attitudes and views between Believers and Infidels in receiving Allah’s favor. Using the methodology of takhrij hadith, it can be concluded that the hadith has the degree of shahih, there is no shadz, ‘illah, or defects in the hadith. All narrators of hadith have the nature of Thiqah so that the hadith can be accepted. [Penelitian ini dilatarbelakangi oleh banyaknya umat Muslim yang kurang sadar akan urgensi mempelajari ilmu hadis serta implementasinya dalam kehidupan. Oleh karena itu, tujuan penelitian ini adalah untuk mengkaji suatu hadis terkait larangan makan berlebihan dalam kitab Mu’jam al-Kabir karya Imam at-Thabrani sebagai salah satu upaya dalam implementasi ilmu hadis. Penelitian ini juga bertujuan untuk memberikan pemahaman kepada masyarakat Muslim agar terhindar dari penyakit yang merugikan kesehatan sebab makan berlebihan. Adapun hasil dari penelitian ini adalah dalam kitab Mu’jam al- Kabir dijelaskan bahwa Nabi Muhammad mengumpamakan orang yang makan berlebih layaknya orang kafir yang kurang bersyukur akan nikmat Allah. Sebaliknya, dikatakan bahwa orang Mukmin yang bersyukur akan mengerti bagaimana adab yang benar terhadap Allah dan tidak menjadikan materi sebagai tujuan dari hidupnya. Oleh karena itu, dapat dilihat perbedaan sikap dan pandangan antara orang Mukmin dan Kafir dalam menerima nikmat Allah. Dengan menggunakan metodologi takhrij hadis, dapat disimpulkan bahwa hadis tersebut memiliki derajat shahih, tidak ada syadz, ‘illah, maupun kecacatan dalam hadis. Serta keseluruhan perawi hadis memiliki sifat Thiqah sehingga hadis tersebut dapat diterima.]